Using Mobile Devices & Social Media in Supporting Engineering Education - Khan, M. M. H; Chiang, Jeffrey C. L. (2014)
Smart phones are used worldwide due to their enhanced features, such as computing power, increased storage capacity, attractive interface, Wi-Fi connectivity and upload capabilities. These are personal, portable and being increasingly used to assist students’ learning that creates new educational opportunities for students at university. Social media ,on the other hand, has emerged in the last decade as a dominant feature of the technology landscape, especially for our current generation of digital-native students. Leveraging these tools for higher education in general, and engineering education in particular, should be of immediate and pressing concern for educators. This research will investigate how students at university use smart phones with respect to engagement and interaction in various learning activities. It will study how students engage with learning tasks and what social interactions occur when they are trying to achieve their academic goals. Also, the tools/software that supports their academic goals in different learning settings or activities will be considered. This paper shows the background of the research to promote engineering students’ learning curve.